Obstacles build communication and coordination of institution in the university: a qualitative study - Zahara Tussoleha Rony; Suharjuddin Suharjuddin; Tatar Bonar Silitonga (Jurnal Siasat Bisnis)
The Corona Virus Pandemic forces most organizations to implement systems and policies that are adjusted to gov-ernment regulations and appeals, including work from home, including at a research institute in private universi-typies in Indonesia. For the systems and policies to be implemented effectively, the leadership makes adjustments, especially in managing communications. Communication management is an important point during this transi-tional period because it has an impact on the coordination and results of work. Ineffective communication causes the institution's performance to be less than optimal. The purpose of this research is to describe the practice of communication management and coordination carried out by the leadership of an institution at a private university in Jakarta. The research method chosen was a case study approach, 11 informants were determined by purposive and snowball sampling. The results of this research show that the communication and coordination carried out by the leadership of the institution is not optimal, besides that it is limited to taking the initiative in confirming and providing a response, resulting in delays in completing their work. The fact in the field of leadership has not ad-justed the style of communication and coordination during the new normal. Comprehensive communication and coordination skills need serious attention because these abilities have an impact on institutions in building a cul-ture of synergy.